Community-directed interventions for priority health problems in Africa: results of a multicountry study (2010)
Objective: To deterrnine the extent to which the community-directed approach used in onchocerciasis control in Africa could effectively and efficiently provide integrated delivery of other health interventions. Methods: A three-year experirnental study was undertaken in 35 health districts from 2005 to 2007 in seven research sites in Carneroon, Nigeria and Uganda. Four trial districts and one comparison district were randomly selected in each site. All districts had established ivermectin treatment programmes, and in the trial districts four other established interventions - vitamin A supplementation, use of insecticide-treated nets, home management of malaria and short-course, directly-observed treatment for tuberculosis patients - were progressively incorporated into a community-directed intervention (CDI) process. At the end of each of the three study years, we performed quantitative evaluations of intervention coverage and provider costs, as well as qualitative assessments of the CDI process. Findings with the CDI strategy, significantly higher coverage was achieved than with other delivery approaches for all interventions except for Short-course, directly-observed treatment. The coverage of malaria interventions more than doubled. The district-level costs of delivering all five interventions were lower in the CDI districts, but no cost difference was found at the first-line health facility level. Process evaluation showed that: (i) participatory processes were important; (ii) recurrent problerns with the supply of intervention materials were a major constraint to implementation; (iii) the communities and community implementers were deeply committed to the CDI process; (iv) community implementers were more motivated by intangible incentives than by external financial incentives. Conclusion The CDI strategy, which builds upon the core principles of primary health care, is an effective and efficient model for integrated delivery of appropriate health interventions at the community level in Africa.